Coimmobilization of l‐methioninase and glutamate dehydrogenase: Novel approach for l‐homoalanine synthesis. (23rd November 2014) - El‐Sayed, Ashraf S.A.; Yassin, Marwa A.; Ibrahim, Hend
Abstract l‐Homoalanine, a nonnatural amino acid that is rarely found in human and microorganisms, is used in the synthesis of various medically pivotal antiepileptic drugs and antituberculosis compounds. l‐Homoalanine can be synthesized by different enzymatic approaches. In this article, the synthesis of l‐homoalanine from l‐methionine was explored by coimmobilization of Aspergillus flavipesl‐methioninase (AfMETase) and glutamate dehydrogenase (GDH) on polyacrylamide and chitosan. Polyacrylamide coimmobilized AfMETase and GDH displayed a maximum reactivity for the synthesis of homoalanine from l‐methionine. The chitosan‐coimmobilized AfMETase and GDH retain about 70% of their initial activity of l‐homoalanine production by the fifth catalytic reusability cycle as compared with 50% for polyacrylamide coimmobilizate. Catalytic conditions were optimized for the maximum yield of homoalanine. Homoalanine was purified by cationic and anionic chromatographs and the proton nuclear magnetic resonance (H‐NMR) analysis of the lyophilized sample displayed a unique chemical structure identical to the authentic homoalanine. Using dependable dual action of AfMETase and GDH immobilized on a solid support is a novel approach for in vitro enzymatic synthesis of l‐homoalanine from l‐methionine, and the immobilized enzymes can be reused many times without any significant loss of their activities.